An efficient cleanup method coupled with gas chromatography and mass spectrometry for multi‐pesticides residue analysis in complex plant matrices. Issue 11 (June 2017) - Wang, Xinquan; Qi, Peipei; Wang, Xiangyun; Zhang, Qian; Wang, Zhiwei; Xu, Xiahong; Xu, Hao; Zhang, Hu; Wang, Qiang
Abstract : We aimed to develop an efficient cleanup method for multi‐pesticides residue analysis in complex plant matrices, shallot, ginger, garlic, onion, leek, and celery. Column chromatography was used as the cleanup method and fabricated with florisil and graphitized carbon black as the adsorbents. The amount of the graphitized carbon black adsorbent and the choice of the elution solvent were systematically investigated for exploring the best combination. The target pesticides covered organochlorine, pyrethroid, and organophosphorus pesticides, and were 38 in total. The method validation and comparison were performed to verify its feasibility and advantages in operation convenience and purification efficiency. The method limit of quantitation varied from 0.01 to 0.03 mg/kg, which depends on the pesticides and the sample matrices. The recoveries of the pesticides ranged from 60.5 to 128% (RSD ≤ 19.0%) at the spiked concentration level of 0.01 (or 0.03) mg/kg and 62.9 to 130% (RSD ≤ 13.0%) at 0.1 mg/kg. Compared with the commercial cleanup solid‐phase extraction cartridges, the present adsorbent combination displayed better purification effect and shorter sample pretreatment time, demonstrating potential application prospect in the complex matrix sample analysis.